THE EFFECT OF "VOKADIN" MEDICATION IN COMPLEX TREATMENT OF PURULENT - INFLAMMATORY PROCESSES IN PATIENTS WITH THE DIABETIC FOOT SYNDROME - Нємченко, І.І.; Ляховський, В.В.; Дудченко, М.О.; Ковальов, О.П.; Cradle, A.M.; Кравців, М.І.; Кизименк, О.О.; Нємченко, Л.Б.; Kravchenko, I. (World of Medicine and Biology, 2015)
A survey of 58 patients with purulent - inflammatory soft tissue foot who were treated at the surgical department №1 2nd MCL m. Poltava, in which the treatment of locally applied antiseptic preparation "Vokadin." Investigated indicators of clinical course of wound healing and microbiological contamination of wounds. Results of clinical - laboratory studies found that topical application of the drug "Vokadin" in the complex treatment of purulent - inflammation of the soft tissue in the feet of diabetic patients makes it possible to shorten antibiotic therapy and speeds healing that positively affects both clinical and the effect of pharmacoeconomic treatment.
Keywords: wound process; iodoform; surgical infection